Social impact of green roofs - Nguyen Dang, Hoai-Anh; Legg, Rupert; Khan, Aila; Wilkinson, Sara; Ibbett, Nicole; Doan, Anh-Tuan (Frontiers in Built Environment, 2022)
Green roofs are contribute towards building-related energy efficiency. Since roofs account for 20-25% of all urban surface areas, it is not surprising that such a green system can decrease energy consumption. The current literature on green roofs mostly focuses on the eco-benefits of such structures. A handful of research papers have theorised that as green roofs become more prevalent, there will be associated social outcomes for an urban community. However, empirical work in this space is minimal. This research addresses this gap and contributes to the literature by providing an insight to city dwellers’ social experiences when using a green roof space. This study identified a green roof space in central Sydney, Australia: the Alumni Green at the University of Technology Sydney. The roof, containing a garden, a concrete open space and a raised grass area amounting to 1,200 m2, is above parts of the university’s library and classrooms, and is easily accessible by staff, students, and members of the public. Two members of the research team conducted surveys on site. Some green-roof users were also contacted via email. Over 128 individuals began the survey, although after removing responses that were incomplete or contained errors, 104 responses remained. The findings revealed that users most commonly relaxed or socialised on the green roof, with exercise a far less frequent use. Further, those who frequented the green roof once a week or more reported significantly greater social well-being and attachment to place than those who visited less. Likewise, those who visited the green roof for periods of 30 minutes or more also reported greater social wellbeing. There were no significant differences between frequency and length of use and users’ perspectives on the green roof’s economic, physical, collective identity or environmental impacts. These present findings have implications for urban and landscape designers, as they reveal that green roofs have similar social and place-attachment benefits to those observed of green spaces in the literature. Given that green roofs can fit in places that parks or other open spaces often cannot, their implementation should be encouraged to promote social well-being and place attachment.